Evaluation of User Satisfaction of IBI Library Application Using PIECES Model - Dintia Amalia, Silvyani Yasyfa Kamseno, Amanda Aprilia Harahap, Rahmat Iqbal, (Jurnal El-Pustaka, 2024)
The writing of this article discusses the users and use of the IBI library application using the pieces model. By using pieces analysis as a tool to analyze a system in detail and thoroughly which will get special attention, so that the advantages and disadvantages of the system can be known to later be used as a reference for the company's further progress. PIECES is a best learning practice and development initiative that provides an approach to understanding and improving care for individuals with complex physical and cognitive needs and behavior change. PIECES enables the continuous improvement of shared care through human resource development.  In the PIECES framework there are six components that can be used in evaluating the satisfaction of information system users, namely Performance (Reliability), Information, Economy, Control (control), Efficiency and Service. This study uses a quantitative descriptive research method which aims to describe, summarize, various conditions, various situations or variables that arise in the community which is the object of research. The population and samples in this study were users of the IBI library application with a total of 15 respondents and the sampling technique in this study using random sampling. To get the results of the evaluation of the system, data measurement is needed. In this study, the data measurement method used a Likert scale with the criteria SS (Strongly agree) with a score of 4, S (Agree) with a score of 3, TS (Disagree) with a score of 2 and STS (Strongly disagree) with a score of 1. The purpose of this study was to evaluate the IBI library application to determine user satisfaction with the IBI library application.